A mobilidade do quarteto instrumental Yangos: dos fluxos às redes. Turismo, território e música - De Sá, Felipe Zaltron (My University, 2021)
In its marks, Post-Modernity sensitizes the new contemporary moment in aspects as: [a] the paradigmatic ruptures of science in which cartesianism is faced with visions that consider subjectivities and complexities in the subject-researcher relationship and the researched object; [b] dislocations, fragmentations and space-time compressions, also assuming the 'erasure of the territory'; [c] the territory, in its transversalities, marked by multiterritoriality, de-reterritorialization and network-territory; [d] the increasing mobility of social, cultural, space-time, economic, political and ideological relations that modify the structures of subjects, objects, information and capital; [e] cultural relations, especially music, in differentiations in their phenomenon analyzed by scalar logics, mainly for its conceptual expansion and space-time compression; [f] the formation of networks, which mix place, territory and culture, mobilizing [i]mobile structures; [g] Tourism encompassing and challenging these dialogic and trying to understand them in their complex multidimensions. Considering such scenarios, this research has as its object of study, Tourism seen through Mobility, Territory, Place and Music, interwoven with networks. From the theoretical constructions, analyses the subjects of the instrumental quartet Yangos, who in their movements and displacements through territories and places built and formed networks: macro and micro, subjective and musical. Methodologically, considers the complexity and mobility to be carried and intertwined by and with the subjects-researched, which made it possible to research the complexus and on the move. With this, the problematizing question starts from which the possible approximations and distances are signaled in the contemporary postmodern relations between mobility, territory, place and music analyzed through flows and networks, if associated with Tourism and considering the instrumental quartet Yangos, as an empirical object. The general objective is to describe the dialogue of the instrumental quartet Yangos with the topologies [root] and topographies [rhizome] in network intertwining with Tourism and the musical network. Exploring the possibilities of approximations and distances, it is understood that topology and topography are part and form networks, as part of the mobility of their structures, in rooting and in the rhizome. Both formations carry dialogical characteristics that contribute to the construction of the network formation. Analyzing the mobility[ies] of the instrumental quartet Yangos, three formations emerge, which is called in the scope of this research: rooted score, instrumental rhizome and Yangos network. The Yangos network, as formed by the previous two, is constituted as a mobile structure, which seeks the multiple, in its de-reterritorializations, in its [multi]territorialities and in its musics. When accompanying Yangos, for six months, in his performances, his events and in his places of work and residence, pointed out the existence of the three formations, as well as contemporary relations of mobility, territory, place and music. And in this way, interlaced to Tourism, which as a mobile structure displaces the subjects through the different territories and places, exploring performativity and experience as significant. The concepts of Tourism, Mobility, Territory, Place and Music presuppose the interlacing and formatting in networks, which currently expand the discussions about their own disciplines, and reformulate socio-cultural dynamics and practices. [resumo fornecido pelo autor]
Em suas marcas, a Pós-Modernidade sensibiliza o momento contemporâneo em aspectos como: [a] as rupturas paradigmáticas da ciência, em que o cartesianismo se vê defrontado com visões que consideram as subjetividades e complexidades da relação sujeito-pesquisador e o objeto pesquisado; [b] os desencaixes, as fragmentações e as compressões espaço-temporais, pressupondo também o `apagamento do território?; [c] o território, nas suas transversalidades, marcado pela multiterritorialidade, des-reterritorialização e território-rede; [d] a crescente mobilidade das relações sociais, culturais, espaço-temporais, econômicas, políticas e ideológicas que modificam as estruturas dos sujeitos, objetos, informações e capital; [e] as relações culturais, em destaque a música, em diferenciações no seu fenômeno analisado pelas lógicas escalares, principalmente pela sua expansão conceitual e compressão espaço-temporal; [f] a formação das redes, que mesclam lugar, território e cultura, mobilizando estruturas [i]móveis; [g] o Turismo abarcando e interpelando tais dialógicas e tentando compreendê-las em suas multidimensões complexas. Considerando tais cenários, a presente investigação tem como objeto de estudo, o Turismo visto por meio da Mobilidade, do Território, do Lugar e da Música, entrelaçado pelas redes. A partir das construções teóricas, analisa-se os sujeitos do quarteto instrumental Yangos, os quais em seus movimentos e deslocamentos por territórios e lugares construíram e formaram redes: macro e micro, subjetiva e musical. Metodologicamente, considera-se a complexidade e a mobilidade a serem carregadas e entre-laçadas pelos e com os sujeitos-pesquisados, o que possibilitou pesquisar o complexus e em movimento. Com isso, a pergunta problematizadora parte-se de quais as possíveis aproximações e distanciamentos são sinalizados nas relações pós-modernas contemporâneas entre mobilidade, território, lugar e música analisadas por meio dos fluxos e das redes, se associadas ao Turismo e ao quarteto instrumental Yangos, como objeto empírico. O objetivo geral é de descrever o diálogo do quarteto instrumental Yangos com as topologias [raiz] e topografias [rizoma] em rede entrelaçando com o Turismo e a rede musical. Explorando as possibilidades das aproximações e distanciamentos, entende-se que a topologia e a topografia fazem parte e formam as redes, como parte da mobilidade de suas estruturas, no enraizamento e no rizomático. Ambas formações carregam características dialógicas que colaboram para a construção da formação da rede. Analisada a[s] mobilidade[s] do quarteto instrumental Yangos, emergem três formações, a que se denomina no âmbito desta investigação: partitura enraizada, rizoma instrumental e rede Yangos. A rede Yangos, como formada pelas duas anteriores, se constitui como estrutura móvel, que busca o múltiplo, nas suas des-reterritorializações, nas suas [multi]territorialidades e nas suas músicas. Ao acompanhar, a Yangos, durante seis meses, em suas performances, seus eventos e em seus locais de trabalho e residência, apontou-se a existência das três formações, assim como das relações contemporâneas de mobilidade, território, lugar e música. E dessa maneira, entrelaçado ao Turismo, que como estrutura móvel desloca os sujeitos pelos diferentes territórios e lugares, explorando a performatividade e a experiência como significantes. Os conceitos de Turismo, Mobilidade, Território, Lugar e Música pressupõem os entre-laçamentos e formações em redes, que atualmente ampliam as discussões sobre suas próprias disciplinas, e reformulam as dinâmicas e práticas socioculturais. [resumo fornecido pelo autor]
Keywords: Turismo; Mobilidade; Música; Tourism; Mobility; Music